Il Protesilao lucianeo e il destino della sua sposa: l’ambientazione cronologica dei Dialoghi dei morti 27 e 28 - Paola Dolcetti (Annali Online dell'Università di Ferrara. Sezione Lettere)
Lucian dedicates the Dialogues of the Dead 27 and 28 to Protesilaus. In the first dialogue the hero tries to find out where the responsability of his destiny, that deprived him of his wife, lies. In the latter, he begs Pluto to allow him to come back among the living men for a day: so he could see his wife again.